Evaluation of residual stress on shot peened spring steel surface by X-ray cosα method - Tomohiro YAMAZAKI; Yuji SODA; Takuya YAMAOKA; Toshihiko SASAKI (Nihon Kikai Gakkai ronbunshu, 2021)
The purpose of this study is to carry out the basic verification necessary for the correct evaluation of the residual stress of shot peened spring steel by the cosα method. Spring steel (JIS-SUP9) was used as the specimen. Shot peening (SP) was performed on the surface of the specimen by changing the direction and the number of SP. In the X-ray stress measurement, the Debye ring was measured from five directions for each measurement point and used to determine the residual stress. We also examined the effects of changing X-ray incident angles. Residual stress was determined assuming plane stress or tri-axial stress, respectively. As a result, it was found that out-of-plane shear stress (τxz) may occur depending on the direction of SP, and in that case, if stress analysis assuming plane stress is performed, a measurement error will occur. Furthermore, it was found that the smaller the incident angle of X-rays, the larger the measurement error.